Immediate reinfection with Omicron variant after clearance of a previous SARS-CoV-2 infection - Antonella Mencacci; Alessio Gili; Barbara Camilloni; Giulia Bicchieraro; Roberta Spaccapelo; Carla Bietta; Fabrizio Stracci (Elsevier, 2022)
SARS-CoV-2 Omicron variant is spreading worldwide, causing unprecedented epidemic peaks due to its transmissibility and immune evasion. We searched in the archive of the Regional Microbiology Laboratory (Umbria, Italy) for immediate reinfection (i.e. infection occurring 25-60 days from primary infection) among 454,764 RT-PCR tests from 261,217 individuals. Lineage heterogeneity was assessed by S gene target failure phenomenon or whole genome sequencing. We found that BA.1 Omicron variant may cause immediate reinfection of patients just recovered from Delta infection. Immediate reinfection was not observed for any other combination of variants, including Delta over Alpha variant and BA.2 over BA.1 Omicron lineage.